33Patterns of antithrombotic therapy in relation to type of atrial fibrillation: insights from the UK cohort of the global GARFIELD registry. - Apenteng, P; Murray, E; Hobbs, F; Kakkar, A; Fitzmaurice, D (2014)
UNLABELLED: Evidence based atrial fibrillation (AF) management guidelines recommend oral anticoagulation (OAC) for patients with atrial fibrillation at moderate to high risk of stroke and without contraindications regardless of type of atrial fibrillation. The literature suggests a misconception about stroke risk in relation to type of AFresulting in a significant proportion of patients with paroxysmal AF not receiving prophylactic anticoagulation. It is unclear if this misconception persists in clinical practice. Using UK data from a global AF registry we investigated the use of antithrombotic therapy according to CHADS2score and type of AF. METHODS: GARFIELD-AF is an on-going, observational, international registry of newly diagnosed AF patients with at least one additional investigator-determined risk factor for stroke. The registry aims to enrol 50,000 prospective patients and 5000 retrospective patients in five independent, sequential cohorts. The study is designed to enrol consecutive eligible patients, and participants are followed up for a minimum of 2 years. Data collected at baseline include patient demographics, medical history, and treatments initiated at diagnosis. Data is also collected on type of AF using the current AF classification scheme consisting of paroxysmal, persistent, and permanent AF, plus a fourth classification 'new AF' for cases where AF has not yet been classified. Stroke risk scores were calculated retrospectively for CHADS2. RESULTS: Out of 10,614 cohort one participants, 397 were enrolled in the UK. These results relate to the UK population. Approximately half (49.6%) of the participants had permanent AF, 12.1% had persistent AF and 18.9% had paroxysmal AF; the remaining 19.4% were classed as 'new' or not yet classified AF. Almost two thirds of the patients (62%) had a high risk of stroke with a CHADS2 score of ≥ 2; a score of 1 and the remaining 4% had a CHADS2 score of 0. Overall the use of OAC was greatest in patients with persistent AF (65.2%) and least in patients with paroxysmal AF (44.8%). In patients at high risk of stroke (CHADS2 score of ≥ 2) patients with paroxysmal AF were least likely to receive OAC (38.5%) compared with patients with permanent AF (61.7%) and persistent (63.6%). Conversely less than half (47.2%) of patients with 'new' unclassified AF with CHADS2 score of ≥ 2received OAC. IMPLICATIONS: This UK dataset suggests OAC use is influenced by type of AF. Patients classified as having paroxysmal AF were least likely to receive anticoagulant treatment and there was underutilisation of anticoagulation for patients in this category. The stroke risk with paroxysmal AFis comparable to that of permanent AF therefore it is important that all AF patients irrespective of type of AFare considered for OAC use in accordance with guideline recommendations.